English language teachers’ literacy competence in literature - Prasetyo Hazairin Eko; Kurniati Victa Sari Dwi; Kusuma Adhi (UAD TEFL International Conference)
The study was carried out to describe English teachers’ literacy competence in English literature which had a very important role in the teaching of English language through literature to strengthen character educational values. The study applied descriptive statistics in the forms of frequencies “to describe and summarize the data.” In reporting the data, percentages were used (Leavy, 2017: 111). The respondents of the study consisted of fifteen English language teachers working for five senior high schools organizing special interest classes in languages. The techniques for collecting data were questionnaires and FGD (focus group discussion). The data were analyzed by using quantitative descriptive techniques consisting of central tendency and percentage analysis. The results of the study showed that all the teachers got between two and fourteen credits in literature from their undergraduate colleges. Their reading hours in literature after graduation did not show any regular base. This was particularly due to the fact that the portion of literature materials to be taught to the students was very limited. Thus, they thought that it was not necessitated to develop literary competence to support their teaching activities. However, all of them agreed that the teaching of literature to high school students was important and useful to improve their language skills as well as their character educational values.